Hybrid optimization method for optimal site selection and sizing of a hybrid photovoltaic water pumping/diesel/battery system - Akbar Maleki; Fatemehzahra Heydari; Ali Jabari Moghadam (Heliyon)
In this paper, a hybrid optimization method based on a technique for order of preference by similarity to an ideal solution (TOPSIS) is used for the simultaneous site selection and sizing of a hybrid photovoltaic (PV) water pumping/diesel generator energy system. Various sites in Iran are analyzed for the establishment of the photovoltaic water pumping power plants. Key geographical and climatic criteria are used for optimal site selection across different sites. Following this, technical and economic optimization of the hybrid energy scheme is conducted with the aim of maximizing reliability and minimizing costs to meet the water requirements for a 12-ha grain field and a household. The optimal number of components, including solar panels, batteries, converters, and diesel generators, are determined. Additionally, the role of an energy storage device (battery) is carefully evaluated with respect to key parameters such as initial investment cost and fuel consumption rate of the proposed hybrid systems. The results indicate that Sarayan in South Khorasan province, Beydokht 2 in Razavi Khorasan province, and Jajrom in North Khorasan province are the most suitable locations for establishing photovoltaic water pumping systems. Moreover, the optimal sizing of the three proposed hybrid energy systems (1.PV/Diesel/Battery, 2.PV/Diesel, and 3. PV/Battery) reveals that the PV/Diesel/Battery hybrid system offers the lowest costs and highest reliability. Finally, a sensitivity analysis is conducted on component prices, interest rates, and fuel prices to examine the results.